2013
DOI: 10.1038/aps.2012.206
|View full text |Cite
|
Sign up to set email alerts
|

FGFR4 genetic polymorphisms determine the chemotherapy response of Chinese patients with non-small cell lung cancer

Abstract: Aim: To investigate the relationship of fibroblast growth factor receptor 4 (FGFR4) gene polymorphisms with the response of Chinese patients with non-small cell lung cancer (NSCLC) to chemotherapy. Methods: A total of 629 patients with Stage III (A+B) or IV NSCLC, as well as 729 age-and gender-matched healthy controls were recruited. All the patients received platinum-based chemotherapy, and the therapeutic effects were evaluated. Three polymorphisms in the FGFR4 gene (rs351855G/A, rs145302848C/G, and rs147603… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…However, contradictory results have been reported in other studies. In a work involving advanced NSCLC Asian patients, the FGFR4-388Arg variant correlated with better outcome 17 , and in another study involving Caucasian NSCLC patients, no association between this FGFR4 variant and outcome was found 18 . In some retrospective studies of lung cancer cohorts analyzing each histological subtype independently, the FGFR4-388Arg variant was linked to lymph node involvement and poorer overall survival (OS) in ADC patients 13 , 16 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 92%
“…However, contradictory results have been reported in other studies. In a work involving advanced NSCLC Asian patients, the FGFR4-388Arg variant correlated with better outcome 17 , and in another study involving Caucasian NSCLC patients, no association between this FGFR4 variant and outcome was found 18 . In some retrospective studies of lung cancer cohorts analyzing each histological subtype independently, the FGFR4-388Arg variant was linked to lymph node involvement and poorer overall survival (OS) in ADC patients 13 , 16 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, the FGFR4 rs351855 CT/TT genotypes sustained receptor activation and improved stability of the receptor more than did the CC genotype. This suggested influence on the response to chemotherapy in HCC patients treated with tyrosine kinase inhibitors [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 95%
“…The role of the FGFR4-388Arg variant as a prognostic factor in lung cancer has been previously addressed in the literature, but little work has focused on the role of this variant in SCC patients. In several cohorts jointly analyzing ADC and SCC patients, controversial results have been reported, [12][13][14] probably as a result of the different ethnicities and clinicopathologic characteristics of the patients included in these study cohorts. Nevertheless, none of these studies analyzed SCC patients independently.…”
Section: Role Of Fgfr4-388arg Variantmentioning
confidence: 99%
“…However, the implications of this variant in patient prognosis seem to be controversial in studies that jointly analyze multiple histologic subtypes of NSCLC. [12][13][14] Nonetheless, other studies that analyze the different NSCLC subhistologic types individually have shown that the FGFR4-388Arg variant is related to poorer overall survival (OS) in several cohorts of ADC patients. 15,16 In an SCC patient cohort analysis, however, the correlation between this variant and outcome was not clear.…”
Section: Introductionmentioning
confidence: 99%